Biohacking: Garage Transhumanism (Revista Iberoamericana de Bioética, 2021)
Biohacking is a grass-roots movement that brings the knowledge and experimental practice of biological sciences to a non-specialized public. This article seeks to identify biohacking as a type of transhumanism and not just as a movement influenced by the latter. To do so, it examines the constitution, history, practices, and moral codes of the biohacker movement. Subsequently, it compares the results with the definition of transhumanism, finding points of similarity in the hypotheses of both, as well as an adaptation of transhumanist values to biohacking. It concludes by identifying biohacking as a type of transhumanism.
Keywords: biohacking; cyborg; DIYBio; grinder; transhumanism